2020
DOI: 10.1002/acn3.51066
|View full text |Cite
|
Sign up to set email alerts
|

Relation of plasma β‐amyloid, clusterin, and tau with cerebral microbleeds: Framingham Heart Study

Abstract: Objective: Cerebral microbleeds (CMBs) are associated with higher risk of stroke and dementia, predating clinical diagnosis by several years. CMB are considered markers of cerebral small vessel disease (CSVD): hypertensive (deep CMB) and cerebral amyloid angiopathy (lobar CMB). We related plasma b-Amyloid (40, 42 and their ratio), clusterin, and tau levels to CMB to elucidate their role as biomarkers for the angiopathies represented by CMB. Methods: Dementia, stroke, and other neurological disease-free Framing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Using cerebrospinal fluid may have had a higher predictive value [ 57 , 116 , 117 , 118 ]. Elevations in serum NF-L levels were reported inconsistently in studies plagued with small fibers, unadjusted for comorbidities, or limited to the most sick patients [ 12 , 32 , 35 , 94 , 119 , 120 , 121 ]. Gisslen et al reported the normalization of GFAP and NF-L six months after the resolution of COVID-19, but their patients continued to exhibit neurological symptoms and their study was limited to these markers [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Using cerebrospinal fluid may have had a higher predictive value [ 57 , 116 , 117 , 118 ]. Elevations in serum NF-L levels were reported inconsistently in studies plagued with small fibers, unadjusted for comorbidities, or limited to the most sick patients [ 12 , 32 , 35 , 94 , 119 , 120 , 121 ]. Gisslen et al reported the normalization of GFAP and NF-L six months after the resolution of COVID-19, but their patients continued to exhibit neurological symptoms and their study was limited to these markers [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gisslen et al reported the normalization of GFAP and NF-L six months after the resolution of COVID-19, but their patients continued to exhibit neurological symptoms and their study was limited to these markers [ 34 ]. Persistent elevations of several neurodegeneration markers suggest an ongoing pathological process in COVID survivors that is heterogeneous [ 38 , 43 , 44 , 46 , 51 , 52 , 55 , 87 , 94 , 111 , 122 ]. This indicates a potential mechanism for post-COVID-19 cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…24 Reproducibility of CMB ratings in the FHS is good to excellent. 25 Presence of CMBs were categorized according to their brain location: any CMB (CMB in any brain region), lobar only, deep only, and mixed location (lobar or deep).…”
Section: Cerebral Microbleedsmentioning
confidence: 99%